Involving Parents in Cognitive-Behavioral Therapy for Child Anxiety Problems: A Case Study. (August 2014) - Siddaway, Andy P.; Wood, Alex M.; Cartwright-Hatton, Sam
This case study examines how parents can be incorporated into all aspects of cognitive-behavioral therapy (CBT) for child anxiety problems. This is an important issue, because although there are strong theoretical and empirical reasons for incorporating parents into treatment, evidence from randomized controlled trials has so far been inconclusive about whether outcomes are improved by involving parents. This case study describes the clinical benefits of a balanced focus on parent and child factors for "Laura, " an 8-year-old girl experiencing a range of fears and worries, including refusing to attend school. Treatment consisted of seven sessions of CBT, which targeted parent and child factors hypothesized to be critical to the development and maintenance of Laura's anxiety problems. The clinician's decision making and reasoning in carefully selecting CBT interventions to specifically address the presenting problems are illustrated. Laura showed marked reductions in avoidance behaviors and fears and returned full-time to school.